Pengaruh Pejantan dan Pakan terhadap Pertumbuhan Itik Turi sampai Umur delapan Minggu (The Effect of Sires and Diets on the Growth of Turi Duck Until the Age of 8 Weeks) - Ratih Dewanti; Jafendi Hasoloan Purba Sidadolog; Zuprizal (Zuprizal) (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
The experiment was carried out to observe the effect of sires and diets on the growth traits of Turi duck up to the age of eight weeks. There were five sires and 25 dams which produced 151 offspring used in the experiment. Three diets with equal nutrient balance but different concentration P1: CP:EM= 1:145,EM 2482 kcal/kg:protein 17%; P2 CP:EM= 1:146 EM 2628 kcal/kg:protein 18%; dan P3 CP:EM= 1:144 (EM 2774 kcal/kg: protein 19% were then applied. Phenotypic datasets on body weight, body weight gain, feed consumption and feed conversion parameters were collected. The result showed that sire had no effect on body weight, body weight gain and feed conversions of the offspring. Different diets, on the other hand affected feed consumption (lowest P3:822.37 g/head/weeks). Interactions between sires x age were then found to be significantly affected feed consumption.(Key words: Sires, Diets, Growth, and Turi duck)